Canonical autophagy does not contribute to cellular radioresistance. Issue 3 (March 2015) - Schaaf, Marco B.E.; Jutten, Barry; Keulers, Tom G.; Savelkouls, Kim G.M.; Peeters, Hanneke J.M.; van den Beucken, Twan; van Schooten, Frederik-Jan; Godschalk, Roger W.; Vooijs, Marc; Rouschop, Kasper M.A.
Abstract Background (Pre)clinical studies indicate that autophagy inhibition increases response to anti-cancer therapies. Although promising, due to contradicting reports, it remains unclear if radiation therapy changes autophagy activity and if autophagy inhibition changes the cellular intrinsic radiosensitivity. Discrepancies may result from different assays and models through off-target effects and influencing other signaling routes. In this study, we directly compared the effects of genetic and pharmacological inhibition of autophagy after irradiation in human cancer cell lines. Materials and methods Changes in autophagy activity after ionizing radiation (IR) were assessed by flux analysis in eight cell lines. Clonogenic survival, DNA damage (COMET-assay) and H2AX phosphorylation were assessed after chloroquine or 3-methyladenine pretreatment and after ATG7 or LC3b knockdown. Results IR failed to induce autophagy and chloroquine failed to change intrinsic radiosensitivity of cells. Interestingly, 3-methyladenine and ATG7- or LC3b-deficiency sensitized cancer cells to irradiation. Surprisingly, the radiosensitizing effect of 3-methyladenine was also observed in ATG7 and LC3b deficient cells and was associated with attenuated γ-H2AX formation and DNA damage repair. Conclusion Our data demonstrate that the anti-tumor effects of chloroquine are independent of changes in intrinsic radioresistance. Furthermore, ATG7 and LC3b support radioresistance independent of canonical autophagy that involves lysosomal degradation.